Enhancing the learning of subtraction concepts through songs to grade two pupils at Gwenzimukulu primary school - Shanangurai, Ratidzo (Midlands State University, 2018)
The research’s main focus was to enhance the learning of mathematical subtraction concepts through the aid of songs. Attempts were made to help pupils learn mathematical subtraction concepts through the aid of songs. The study was carried out in a second grade class in a rural school called Gwenzimukulu Primary. It is qualitative in nature. An action research was employed in collecting data. Grade Two Red class participated in the study. Convenience sampling technique was used to select the participants as well as the research site. To gather data, the researcher used interviews and observations. Tests and exercises on subtraction were also administered. The findings indicate that songs can be used in varied ways to help pupils learn mathematical subtraction concepts. Teachers in Zimbabwean primary schools are called upon to help all the pupils learn mathematics subtraction concepts through engaging them actively in the learning process.